The flatshare - O'Leary, Beth (Flatiron Books, 2019)
Tiffy and Leon share an apartment in London. Tiffy and Leon have never met. After a bad breakup, Tiffy Moore needs a place to live. Fast. And cheap. But the apartments in her budget have her wondering if astonishingly colored mold on the walls counts as art. Desperation makes her open minded, so she answers an ad for a flatshare. Leon, a night shift worker, will take the apartment during the day, and Tiffy can have it nights and weekends. He'll only ever be there when she's at the office. In fact, they'll never even have to meet. Tiffy and Leon start writing each other notes - first about what day is garbage day, and politely establishing what leftovers are up for grabs, and the evergreen question of whether the toilet seat should stay up or down. Even though they are opposites, they soon become friends. And then maybe more. But falling in love with your roommate is probably a terrible idea... especially if you've never met.